The relationship between water quality and black fly (Diptera: Simuliidae) abundance in Tambunan District, Sabah - Nur Ashiqin Abdul Hamid,; Lardizabal, Maria Lourdes T.; Takaoka, Hiroyuki; Stephen, Estherpeni; Maznah Mahali, (Pusat Sistematik Serangga ,UKM, 2016)
Black flies (Diptera : Simuliidae) have been extensively studied almost worldwide (Hamada & Grillet, 2001). This is because blackflies are among the best-known aquatic insects and globally distributed (Adler et al., 2004). Black flies in Malaysia are less known and research about this aquatic insect is still scarce especially in Borneo region. Most of the earlier studies on black flies in Sabah were related to taxonomy (Takaoka, 2001). However, studies on ecology and the role of black flies as bio-indicator has so far not been well reported yet. The aim of this study is to determine the relationship of water quality against the abundance of black flies pupa (Simuliidae). Regression test shows that relationship between dissolve oxygen (r2=0.57, p=0.02), total dissolve substance (TDS) (r2=0.18,p=0.04) and conductivity (r2=0.14, p=0.04) appeared significant to the abundance of black flies pupae. All the study sites (6 rivers) were classified into Class 1 based on Water Quality Index Classification (DOE, 2006).